The state's responsibility to localize the personal data of its citizens within the framework of international human rights law (Journal of Imam Al-Kadhim College, 2024)
Countries have moved towards localization laws to protect the digital data of their citizens, to keep pace with technological development and control its effects, which places on the state a legal responsibility under international human rights law to balance its powers with the rights and freedoms of its citizens on the one hand, and between providing technological structures that guarantee the protection of that data within State borders and protecting their owners.